2015
DOI: 10.1364/ao.54.004566
|View full text |Cite
|
Sign up to set email alerts
|

Schlieren-based temperature measurement inside the cylinder of an optical spark ignition and homogeneous charge compression ignition engine

Abstract: Schlieren [1, 2] is a non-intrusive technique that can be used to detect density variations in a medium, and thus, under constant pressure and mixture concentration conditions, measure whole field temperature distributions.The objective of the current work was to design a schlieren system to measure line-of-sight averaged temperature distribution with the final aim to determine the temperature distribution inside the cylinder of Internal Combustion engines. In a preliminary step, we assess theoretically the er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Su and Bai (2016) demonstrated that the background-oriented schlieren technique can directly and immediately measure the neutral plane position of an internal fire whirl for a vertical shaft model (Su and Bai, 2016). The Schlieren technique uses the first derivative variation of the refractive index between the light and the flow field, as shown in equation (1) (Aleiferis et al , 2015; Kuehn and Goldstein, 2017): …”
Section: Methodsmentioning
confidence: 99%
“…Su and Bai (2016) demonstrated that the background-oriented schlieren technique can directly and immediately measure the neutral plane position of an internal fire whirl for a vertical shaft model (Su and Bai, 2016). The Schlieren technique uses the first derivative variation of the refractive index between the light and the flow field, as shown in equation (1) (Aleiferis et al , 2015; Kuehn and Goldstein, 2017): …”
Section: Methodsmentioning
confidence: 99%
“…To solve this problem, the high-order total variation regularisation can be introduced in the Abel inversion to reduce the influence of image noise. The quantitative analysis from Liu [78] reveals that for a spatial resolution of 50 μm/pixel, the error could be about 10% for temperature over 2000 K. The error can be reduced by improving the spatial resolution [79]. Therefore, a balance needs to be struck between the spatial resolution and FOV to achieve satisfactory accuracy for a specific observation target.…”
Section: Imaging Processing Of Schlieren Imagesmentioning
confidence: 99%
“…This technique has remarkable advantages like easy to implement, uses conventional light sources, is low cost and is very sensitive [2,3]. This method has been improved to face different types of problems in science and engineering [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23]. Even though initially it was used as a visualization method, it has been used to quantify temperature data in fluid flows [8,9,10,11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays different variant of the optical system has been implemented such as color schlieren [10,11,12], background oriented schlieren [13,14] and calibration schlieren [15,16]. This method has allowed to measure simultaneously temperature and velocity in fluid flows [19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%